Polio Eradication Initiative contribution in strengthening immunization and integrated disease surveillance data management in WHO African region, 2014. Issue 43 (10th October 2016) - Poy, Alain; Minkoulou, Etienne; Shaba, Keith; Yahaya, Ali; Gaturuku, Peter; Dadja, Landoh; Okeibunor, Joseph; Mihigo, Richard; Mkanda, Pascal
Highlights: GPEI made investments on data management in the eradication in polio in the Region. Impact of polio data management support to other programmes is not fully documented. Polio data management system were also used for other interventions. IDSR has improved the data availability with support from Polio funded data managers. Abstract: Introduction: The PEI Programme in the WHO African region invested in recruitment of qualified staff in data management, developing data management system and standards operating systems since the revamp of the Polio Eradication Initiative in 1997 to cater for data management support needs in the Region. This support went beyond polio and was expanded to routine immunization and integrated surveillance of priority diseases. But the impact of the polio data management support to other programmes such as routine immunization and disease surveillance has not yet been fully documented. This is what this article seeks to demonstrate. Methods: We reviewed how Polio data management area of work evolved progressively along with the expansion of the data management team capacity and the evolution of the data management systems from initiation of the AFP case-based to routine immunization, other case based disease surveillance and Supplementary immunization activities. Results: IDSR has improved the data availability with support from IST Polio funded data managers who were collecting them from countries. The data management system developed by the polio team was used by countries to record information related to not only polio SIAs but also for other interventions. From the time when routine immunization data started to be part of polio data management team responsibility, the number of reports received went from around 4000 the first year (2005) to >30, 000 the second year and to >47, 000 in 2014. Conclusion: Polio data management has helped to improve the overall VPD, IDSR and routine data management as well as emergency response in the Region. As we approach the polio end game, the African Region would benefit in using the already set infrastructure for other public health initiative in the Region.